Evaluación de estrés y clima organizacional en los funcionarios del sector público que laboran en la parroquia de Cubijíes - Casillas Cortez, Jessica Yajaira (2025)
This research aimed to evaluate stress levels and the organizational climate among public sector employees in the parish of Cubijíes, as no previous studies of this nature have been conducted in this population. The study employed a descriptive, cross-sectional, bibliographic, and field-based research approach, using a non-experimental design. The primary data collection techniques were observation and surveys. For the assessment of stress, the questionnaire developed by Dr. Villalobos was used, while the organizational climate was measured using a questionnaire based on the parameters established by Chiavenato. These instruments were administered to public sector employees in the parish of Cubijíes. To evaluate the reliability of the stress questionnaire, Cronbach’s Alpha was calculated, yielding a value of 0.879, indicating good internal consistency. The Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy resulted in a value of 0.679, considered acceptable. For the organizational climate questionnaire, Cronbach’s Alpha was 0.933, indicating excellent reliability, while the KMO value was 0.612, suggesting a moderate level of adequacy. After data tabulation, risk levels were determined, and the research hypotheses were tested. The null hypothesis (H₀), which posits no correlation between stress and organizational climate, was accepted. Finally, the results revealed that 70% of participants experienced a moderate level of stress, while 30% reported low stress levels. Regarding the organizational climate, 60% of respondents perceived a low level, while 40% perceived a moderate level. Based on these findings, a proposal was developed to support stress management and foster a more positive organizational climate.